Influence of cooperation work on management continuity of ambulatory cardiovascular care: a cross-sectional exploratory study in Germany - Arnold, Christine; Hennrich, Patrick; Peters-Klimm, Frank; Wensing, Michel (International journal of integrated care, 2023)
Introduction: A wide range of factors influence coordination and continuity of care. The aim of this study was to explore how management continuity of cardiovascular-related ambulatory care is influenced by the following network characteristics: presence of a case coordinator, network reciprocity, network composition and team climate. - Methods: This cross-sectional observational study included three written surveys. The primary outcome management continuity of cardiovascular care was measured with the team/cross-boundary scale in the Nijmegen Continuity Questionnaire. The final analysis comprised a multivariate linear multilevel model with the predictors: presence of a case coordinator, network reciprocity, network composition and team climate. - Results: Eighteen general practices with 83 health workers and 340 patients participated. The linear multilevel regression analysis showed a positive influence of team climate on cross-boundary continuity of care (b-coefficient 0.44, 95% confidence interval 0.09–0.78, p = 0.02). No statistically significant influence was measured for the other predictors. - Discussion: To improve integrated care, therefore, emphasis should also be placed on promoting the team climate within individual practices. Regarding network characteristics, further research is needed, especially in larger practices. - Conclusion: This study showed that team climate had an independent, relevant and statistically significant association with cross-boundary continuity of cardiovascular ambulatory care.
Gesehen am 14.06.2024